Igloo football club - Gorman, Sean; Lusher, D.; Reeves, K. (Routledge, 2016)
The Igloo football club is an AFL club that participated in this Australian Research Council project Assessing the Australian Football League’s Racial and Religious Vilification Laws to promote Community Harmony, Multiculturalism and Reconciliation. Igloo participated in the surveys only. This club and its players and staff have all been deidentified as required by Curtin University’s ethics guidelines.